Assessing the reliability and validity of the sport motivation scale-II using the COSMIN methodology - a systematic review - Zhu, Y.; Yang, Y.; Gao, W.; Tian, H.; Yan, P.; Zhang, C. (Frontiers in Psychology, 2026)
Introduction: The Sport Motivation Scale-II (SMS-II) has been widely employed to assess motivational orientations in athletic populations; however, its measurement properties remain subject to debate. This systematic review aimed to evaluate the measurement properties of SMS-II and synthesize the quality of evidence using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) methodology.